Identifying the influence of various technological techniques on the indicators of the composition of bunches and wine samples of the madras grape variety - Fataliyev, Hasil; Lezgiyev, Yusif; Aghazade, Yahya; Gadimova, Natavan; Heydarov, Elnur; Ismailov, Mehman (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is wine samples obtained by maceration of seeded and seedless skins from the autochthonous Madrasa grape variety. The studies were conducted on the autochthonous Madrasa grape variety the influence of the mechanical composition of the bunch and the applied technological methods on the wine composition and quality indicators of wine was not been studied. For the four variants with different numbers of bunches stored in the tin, the amount of lactic juice in % was 83.85–86.03 %, the structural index was 5.2–6.2, and no big difference was noticed between the variants. The amount of phenolic compounds was higher in the fermentation of the pulp with the seed than without the seed. The amount of phenolic compounds was highest (1.87 gAE/L) during alcohol fermentation, and lowest (1.22 gAE/L) during the rest period. The amount of anthocyanins in peel maceration with seeds was 0.118 gMvd-3-0-glu/u, this amount was 0.137 gMvd-3-0-glu/u in fermentation without seeds. After alcohol fermentation, those indicators were 0.140 and 0.208 gMvd-3-0-glu/u, reaching the maximum, respectively. The samples obtained from the Madrasa grape variety, macerated for 48 and 96 hours, were divided into two parts, one of which was fermented with natural yeasts (TQ) and the other with cultured yeasts (MMQ). The amount of total phenolic compounds and phenolic acids in TQ was lower than that of MMQ samples, and the amount of aromatic compounds, on the contrary, was higher in naturally fermented than in samples fermented with cultured yeasts. These studies are important for production in terms of regulating the number of clusters stored in the barrel and the processes occurring during the stages of wine production. The obtained results can be used in family farms and wineries